Analysis of the Impact of Implementation of Occupational Safety and Health Programs on Productivity: Literature Analysis - Nelfita, Natasyah; Aprinawati, Aprinawati; Lubis, Devi Aprilia; Wijaya, Rangga Hadi; Rumapea, Yesayas Roganda; Sampurno, Muhammad Akbar (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Occupational Safety and Health (OSH) is a fundamental aspect of human resource management that can influence work productivity. This study involves a systematic review of literature from various countries, including Indonesia, Japan, and Saudi Arabia, across different industrial sectors. The results show that companies that integrate OSH into their workplace culture tend to achieve better performance. This conclusion underscores the importance of commitment to OSH as a strategy to enhance productivity and employee well-being. The methodology used is a systematic review of journal articles published between 2019 and 2024, utilizing the Google Scholar database. Out of 20 articles found, 14 that met the inclusion criteria were analyzed in depth. The analysis results indicate that the implementation of OSH programs has a positive and significant impact on work productivity across various industrial sectors. However, some studies also indicate that the effectiveness of OSH programs may vary depending on the context of implementation and other external factors. This research concludes that the success of OSH programs in improving productivity heavily depends on the integration of these programs into the company culture and the commitment of all stakeholders.